Loan to Value Ratio, KPR and KPA in Indonesia: An ARDL Approach - ardely, Novrianti Putri; Ekananda, Mahjus (Universitas Airlangga, 2023)
The COVID-19 pandemic that occurred at the beginning of 2020 has caused economic growth to decline in many countries, including Indonesia. One of the steps taken with the aim of economic recovery is by increasing the consumption in credit channels or non-credit channels, such as social aid. This thesis discusses loan-to-value ratio effects on property loans, KPR, and KPA in Indonesia. Property loans, KPR and KPA, are included in consumer credits, and loan-to-value ratio is one of the macroprudential policy instruments. The method used in this thesis is Autoregressive Distributed Lag linear regression (ARDL) with property credit, KPR, and KPA as the dependent variable, the dummy variable of the loan-to-value ratio as the independent variables, and consumer credit interest rates, gross domestic product and inflation as the control variables. In addition, the interaction variable between the dummy variable of loan-to-value ratio and consumer credit interest rate is also used. The results showed that the interaction variable between the dummy variable of tightening in loan-to-value ratio and consumer credit interest rate is significant to property loans, KPR, and KPA in the long run. Furthermore, GDP and consumer credit interest rates, which are control variables, are also significant to property loans, KPR, and KPA in the long run